Uma abordagem enunciativa da autoria em dissertações argumentativas de alunos do ensino médio - SILVA , Joserlândio da Costa (2017)
The general objective of this research is to investigate the construction of the authorship in argumentative dissertations of High School students. Theoretically, we base the investigation on the dialogic perspective of language, presented by Bakhtin and the Circle. We retake the works of Bakhtin (1993; 2010; 2011; 2013; 2015); Bakhtin/Volochínov (2012), Medviédev (2012), and studies of brazilian researchers, as Faraco (2007, 2009), Francelino (2007, 2013), Brait (2014), Sobral (2009), Marchesan (2014), among others. Once the authorship is understood as a result of an action in which the subject mobilizes himself in a pluri-discursive environment, in order to be marked as an axiological active entity, we consider that the student mobilizes many linguistic and enunciative strategies to print a valorative position in the texts that he/she writes. In this sense, our first specific objective is to identify which strategies the subjects who wrote the essays mobilized. The second is to describe the functioning of such strategies in the tessitura of the textual productions. Considering the methodological aspects, this research adopts a qualitative approach with interpretativist nature. The corpus is constituted by 23 essays of students from the 3rd Year, collected in two public schools from Ceará. The results show that the main strategies used by students to print a valorative positioning in the texts are: 1) quotation marks, 2) argumentative operators, 3) rhetoric or semi-rhetoric questions, 4) recurrence of authority discourses, 5) responsive anticipation of a reply, 6) temporal markers, 7) retaking of events socially shared, 8) resumption of daily common discourses, 9) lexical choice, 10) recurrence of exemplification recourse, 11) resumption of the supporting text and 12) giving the voice to the other. These results confirm the affirmation that analyzing the authorship configuration in textual productions of High School students is a process that must consider, simultaneously, aspects of two natures: architectonic and compositional.